تصور ِ"فلاح" حدیث ِرسولﷺ کے تناظر میں؛ ایک تجزیاتی مطالعہ: An analytical Study of The concept of "welfare" in the context of the Holy Prophet'sﷺ hadith - Khanam, Naveeda; Khan, Dr. Sobia (Al-Amīr Research Journal for Islamic Studies, 2024)
In this age of materialism (in which the advancements of science and technology are on the rise), the majority of Muslims are moving away from religion. They consider the achievement of material desires and comforts as their success and success and consider them as sources of comfort and peace. In the meantime, the human mind is becoming fascinated with the facts of the life hereafter. For this reason, according to them, worldly success is the real success. But despite getting these comforts, they are devoid of mental and emotional satisfaction and peace. The concrete reason for this is the success and prosperity and the real reasons for peace and contentment which have been clarified through the Holy Qur'an and the Hadith of the Prophet (peace be upon him). Therefore, in this paper, the same reasons will be explained in the light of hadith, which are the effective motivation for the entire humanity, especially for the Muslim Ummah, in this era of materialism and in the world of self-centeredness, in adopting the means of achieving well-being in practice. It will prove. Keywords: Welfare, Success, Religion, Holy Prophetﷺ, hadith.